Rendemen dan Mutu Lateks Pekat dengan Kombinasi Teknologi Penggetaran dan Pendadihan - Febrina Delvitasari; Widia Rini Hartari; Sintya Widianti; Maryanti (G-Tech: Jurnal Teknologi Terapan, 2024)
Concentrated latex is a processed natural rubber product with a dry rubber content of 60-64%. Making concentrated latex by centrifugation requires investment in expensive equipment, while making concentrated latex by creaming takes a long time, around 2-3 weeks. One way to speed up the production of concentrated latex is by using a simple tool, namely an orbital vibrator. This research used a Randomized Block Design with 2 factors. Factor I is Vibration Time (V) and factor II is creaming Time (T). The results of the research showed that the length of shaking and creaming time in making concentrated latex had an influence on the yield and quality of concentrated latex except for the pH value, but there was no interaction between these two factors. The quality of concentrated latex that meets ISO 2004 standards is pH (10.1-10.83) and WKM (564.33-618.17 seconds) while KKK (53.74 - 57.64%) and KJP (50.58 – 53.29 %), not yet meeting ISO 2004 standards.